Holocene vegetation and climate variability in the winter and summer rainfall zones of South Africa. (June 2016) - Zhao, Xueqin; Dupont, Lydie; Schefuß, Enno; Meadows, Michael E; Hahn, Annette; Wefer, Gerold
To better understand Holocene vegetation and hydrological changes in South Africa, we analyzed pollen and microcharcoal records of two marine sites GeoB8331 and GeoB8323 from the Namaqualand mudbelt offshore the west coast of South Africa covering the last 9900 and 2200 years, respectively. Our data corroborate findings from literature that climate developments apparently contrast between the summer rainfall zone (SRZ) and winter rainfall zone (WRZ) over the last 9900 years, especially during the early and middle Holocene. During the early Holocene (9900–7800 cal. yr BP), a minimum of grass pollen suggests low summer rainfall in the SRZ, and the initial presence of Renosterveld vegetation indicates relatively wet conditions in the WRZ. Toward the middle Holocene (7800–2400 cal. yr BP), a rather moist savanna/grassland rich in grasses suggests higher summer rainfall in the SRZ resulting from increased austral summer insolation and a decline of fynbos vegetation accompanied by an increasing Succulent Karoo vegetation in the WRZ, which possibly suggests a southward shift of the Southern Hemisphere westerlies. During the last 2200 years, a trend toward higher aridity was observed for the SRZ, while the climate in the WRZ remained relatively stable. The 'Little Ice Age' (ca. 700–200 cal. yr BP) was rather cool in both rainfall zones and drier in the SRZ while it was wetter in the WRZ.